Simple design technique for realizing low-voltage low-power CMOS current multiplier - Tangjit, Jetwara; Tangsrirat, Worapong; Satansup, Jetsdaporn; Surakampontorn, Wanlop (My University, 2015)
A simple circuit design technique for the realization of compact low-voltage low-power CMOS four-quadrant analog current multiplier circuit has been suggested. It is based on the use of the square-law characteristic in the NMOS current squaring function circuit operating in the saturation region. The suggested four-quadrant current multiplier circuit is designed for implementing in TSMC 0.25-μm CMOS technology with a low supply voltage of ±0.75V. To evaluate the circuit performance, the circuit has been simulated by PSPICE program. The simulation results show that the circuit has a linearity error of about 1%, a THD of 1.07% at 100 kHz, the total power consumption of 87.6 μW and -3dB bandwidth of 1.32 GHz.
Keywords: CMOS analog circuits; current multiplier; current squarer; current-mode circuit